2007
DOI: 10.1002/mds.21601
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of thalamic dysfunction in Huntington disease by proton magnetic resonance spectroscopy

Abstract: Our objective was to investigate thalamic neuronal dysfunction in patients with Huntington disease (HD). We performed localized single-voxel proton magnetic resonance spectroscopy (MRS) of the thalamus in 22 HD patients and 25 healthy individuals. The mean age of patients was 48.5 years (ranging from 32 to 71 years). Age at onset varied between 20 and 66 years (mean 38.9 years). The expanded CAG repeat ranged from 40 to 52 (mean 45.2) CAGs. The mean age of control group was 35.4 years, ranging from 19 to 67 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
1
24
2
Order By: Relevance
“…H magnetic resonance spectroscopy (MRS) has previously been evaluated as a biomarker modality in premanifest and early HD. [4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-*These authors contributed equally to this work. References e1-e7 are available on the Neurology Web site at www.neurology.org.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H magnetic resonance spectroscopy (MRS) has previously been evaluated as a biomarker modality in premanifest and early HD. [4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-*These authors contributed equally to this work. References e1-e7 are available on the Neurology Web site at www.neurology.org.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] However, the literature is conflicted with regard to the utility of metabolites such as total N-acetylaspartate (tNAA), a measure of neuronal integ-rity, 12 as potential biomarkers in HD. In an attempt to address these discrepant findings, arising in part from small subject numbers, poorly comparable outcome measures and heterogeneity within patient cohorts, we sought to determine the potential of MRS as an HD biomarker using large numbers of subjects in defined, homogeneous clinical cohorts and examined MRS outcome measures normalized to unsuppressed water rather than metabolites such as total creatine (tCr) which are affected in HD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The motor and cognitive symptoms may, from a strict neuroanatomical point of view, originate from the thalamus. In schizophrenia as well as in Huntington's disease, thalamus has been examined with MRS, and NAA has found to be decreased 33 34…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a lower level of N -acetylaspartate (NAA) was confirmed post-mortem in the putamen and cortex in manifest HD [7]. In vivo altered levels of NAA, creatine, choline, and glutamate have been reported in both premanifest and manifest HD in several brain structures, such as the striatum and thalamus using MRS [9, 11, 12, 24, 25, 31, 32]. However, in contrast, other studies using localized MRS did not detect changes in these metabolite levels in either manifest or premanifest HD [6, 21, 35].…”
Section: Introductionmentioning
confidence: 99%